Human-Centric Functional Modeling and the Convergence of Science - Williams, Andy (My University, 2021)
This paper explores Human-Centric Functional Modeling as a universal modeling methodology with the potential to be used for representing all systems both conceptually and functionally, and it explores what capacity for convergence in our understanding of systems means in terms of Human-Centric Functional Modeling, how that capacity might be quantified, and why Human-Centric Functional Modeling as a methodology might maximize our collective capacity to achieve convergence in our understanding across all sciences and across the systems that those sciences study.
Keywords: Human-Centric Functional Modeling; convergence; science